ANALISIS FINANSIAL INDUSTRI RUMAH TANGGA LANTING DI DESA LEMAHDUWUR KECAMATAN KUWARASAN KABUPATEN KEBUMEN - , RINA PURWANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lemahduwur village is the centre of Lanting industry in Kebumen Regency. Lanting is the exclusive snack from Kebumen, it was made by cassava. Otherwise production of Lanting becomes a culture in Lemahduwur village that was inherited from generation to generation. This research aims to determine the feasibility of home industry Lanting, value added of cassava, and the factors that influence profit of industry. The research was conducted on 30 respondents in home industry Lanting. The analytical method used to analyze the feasibility industry includes profit, capital productivity, business efficiency and Break Even Point (BEP). The value added was analyzed using methods Hayami, and profit factors were analyzed according to the Cobb-Douglass profit function. The data were analyzed using multiple linear regression method, data structured that used is the panel data. The results of the analysis show that the home industry Lanting feasible to be developed according to the analysis of profits, R/C ratio, and break even point (BEP). But according to the analysis of the productivity of capital, home industry Lanting not feasible to be developed. Based on the analysis of value added, cassava can give value added about Rp 1415,53/kg for original Lanting and Rp 1508,84/kg for products Lanting seasoning. According to the analysis of the profit factors, resulted that the profit of home industry Lanting is positive significanly effected by the content of cassava, and the production frequency whereas significantly negative affected by wages labor.